The Influence of Human Resources on MSME Export Capability with Digital Competence as a Mediating Variable: Study on the Manufacturer of Pot Growing Balls (Bobupot), Green Galeria Indonesia Surabaya, and Terracotta Pots UD Gerabah Merah Malang - Ismawati, Lilik; Sudarmiatin; Handayati, Puji (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of human resources (HR) on the export capabilities of Micro, Small, and Medium Enterprises (MSMEs) with digital competence as a mediating variable. The study focused on two MSMEs producing crafts, namely the producer of Bola Tumbuh Pot (Bobupot) Green Galeria Indonesia from Surabaya and the producer of terracotta pots UD Gerabah Merah from Malang. The research method used is a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis technique. Data were obtained through questionnaires distributed to 97 respondents who were employees of the two MSMEs. The results of the study indicate that: (1) The quality of HR has a positive and significant effect on digital competence with a path coefficient of 0.683 (p <0.001); (2) Digital competence has a positive and significant effect on export capability with a path coefficient of 0.572 (p <0.001); (3) The quality of HR has a direct effect on export capability with a path coefficient of 0.317 (p <0.05); (4) Digital competence is proven to significantly mediate the relationship between HR quality and export capability with a partial mediation effect of 0.391 (p<0.01). This study provides theoretical and practical implications for HR development in the MSME sector, especially in increasing export capability through the development of digital competence.